Design an essential introduction - Williams, Gareth (Goodman Fiell, an imprint of the Carlton Publishing, 2015)
"This is an indispensable, clear and concise introduction to the world of design and all its facets--a must-have for all design students and those interested in learning more about the fascinating process that turns good ideas into useful products. Design: an essential introduction invites you to delve into the creative, pragmatic and essentially optimistic world of design and introduces you to the most ingenious and inspiring designs of today." -- Provided by publisher